Review on the application of chemometrics for the standardization and authentication of Curcuma xanthorrhiza - Rohman, A. (2024)
Temulawak (Curcuma xanthorrhiza Roxb.) or Javanese turmeric is one of Indonesia's native medicinal plants and is widely distributed throughout Southeast Asia. Temulawak contains some bioactive compounds having biological activities. The secondary metabolites in temulawak vary widely, depending on the environmental conditions where it grows. Temulawak as a raw material for herbal medicine is often faked with other rhizomes so that the analytical method capable of detecting the adulteration practice of temulawak is needed. The standardization of temulawak is a difficult task because the chemical compounds in temulawak are rather complex. In order to overcome the large and complex data, chemometrics is needed. The purpose of this paper was to highlight the application of chemometrics used during the standardization of temulawak through fingerprinting profile studies. During the literature searching, several databases namely Scopus, Web of Science, Pubmed and Google scholar were explored to get the relevant articles using specific keywords related to the topic. Some chemometrics techniques in combination with several instrumental techniques like spectroscopic and chromatographic methods are successfully used for the characterization and fingerprinting profiling of temulawak. Based on the data synthesized, chemometrics is powerful technique for treating the complex data intended for standardization of temulawak.